Survey on use of PPE by workers of manufacturing pools of polyester reinforced with fiberglass (P.R.F.V) - Geron, Mateus; Geron, Vera Lucia Matias G.; de Jesus, Jociel Honorato (Revista Científica FAEMA, 2023)
[Summary not available]
Keywords: use of PPE; pools of polyester; fiberglass; Emerging